Understanding the Stress Process Among Mexican American Adults Aged 50 and Older in the United States - Muñoz, Elizabeth; Choi, Jean; Thanga Raj Malini, Harshini; Maredia, Asma; Romañach Álvarez, Lourdes S (The journals of gerontology. Series B, Psychological sciences and social sciences, 2025)
Compared to non-Latino White adults, Mexican Americans in the United States are disproportionally exposed to more social, environmental, and economic stress that increase risk for poor physical and mental health outcomes. Despite this, Mexican Americans tend to benefit from a mortality and mental health advantage indicative of unique resilience and risk factors. We assessed stress exposure and appraisals in eight domains among Mexican Americans compared to non-Latino Whites, and evaluated if compared to high acculturation, low acculturation may be associated with lower stress exposure and appraisal in Mexican Americans. We used data from 2,004 participants (49.4% Mexican American; 50.6% non-Latino White; age range = 50-92). Stress exposure was the total of endorsed events and stress appraisal was the average reported severity. Poisson and linear regression models tested race/ethnic (and acculturation) differences in exposure and appraisal. There were no differences in the total number of stress exposures between Mexican American and non-Latino White adults (incidence rate ratio = 1.08 [95% CI: 0.99-1.18]), but the types of stress exposures differed. Compared to Mexican Americans, non-Latino Whites consistently endorsed higher stress appraisal (B = 0.23 [SE = 0.04], p < .0001). Mexican Americans with low acculturation reported lower stress appraisal compared to Mexican Americans with high acculturation (B = -0.45 [SE = 0.05], p < .0001). Results indicate that the stress process among Mexican American adults may differ from traditional propositions and highlight the need for more research on the intricacies of the stress process for Mexican Americans in the United States.